2011
DOI: 10.1002/pon.2060
|View full text |Cite
|
Sign up to set email alerts
|

Getting back on track: evaluation of a brief group psychoeducation intervention for women completing primary treatment for breast cancer

Abstract: Results support the effectiveness of providing a single-session group psychoeducational intervention as a first-step approach to supportive care for women at the end of breast cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 47 publications
(71 reference statements)
0
28
0
1
Order By: Relevance
“…Additionally, we offered a single education and counseling session. However, several studies have shown that brief counseling appeared as effective in reducing anxiety as longer treatments [24, 3840]. Notwithstanding, further research with longer duration of education and counseling, together with a cost effectiveness analysis, may be needed to better elucidate the effect of information and counseling for reducing anxiety in women undergoing HSG.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we offered a single education and counseling session. However, several studies have shown that brief counseling appeared as effective in reducing anxiety as longer treatments [24, 3840]. Notwithstanding, further research with longer duration of education and counseling, together with a cost effectiveness analysis, may be needed to better elucidate the effect of information and counseling for reducing anxiety in women undergoing HSG.…”
Section: Discussionmentioning
confidence: 99%
“…Participant and design characteristics of the 32 studies included in this review are summarized in Table , and outcome and assessment measures are described in detail in Table S3, accessible as supporting information. This review comprised of 32 psychosocial interventions with 8 studies utilizing cognitive behavioral therapy interventions, 7 psychoeducational interventions, 4 support groups, three counseling interventions, 2 mindfulness‐based stress reduction interventions, 2 supportive‐expressive group therapy interventions, 1 psychosexual intervention, one music therapy and progressive muscle relaxation training, and 1 contemplative self‐healing intervention . The review also included 2 studies that combined psychoeducational interventions and peer and social support interventions and 1 intervention that combined cognitive behavioral therapy, social support, and psychoeducational elements .…”
Section: Methodsmentioning
confidence: 99%
“…La mejoría observada, no es únicamente producto del paso del tiempo, sino del aprendizaje de estrategias para facilitar la adaptación y aceptación de la enfermedad y sus posibles secuelas (49)(50)(51)(52)(53) . Por último, podemos distinguir entre aspectos emocionales más variables (miedo, ansiedad, ilusión por las cosas) y más estables (tendencia a la ira, insatisfacción con el aspecto físico, efectos en la concentración).…”
Section: Discussionunclassified